2014
DOI: 10.1007/s11154-014-9289-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of GLP-1 on appetite and weight

Abstract: Glucagon-like peptide 1 (GLP-1) is a cleavage product of the pre-proglucagon gene which is expressed in the α-cells of the pancreas, the L-cells of the intestine, and neurons located in the caudal brainstem and hypothalamus. GLP-1 is of relevance to appetite and weight maintenance because it has actions on the gastrointestinal tract as well as the direct regulation of appetite. It delays gastric emptying and gut motility in humans. In addition, interventricular injections of GLP-1 inhibit food intake, independ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
172
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 229 publications
(183 citation statements)
references
References 73 publications
9
172
0
2
Order By: Relevance
“…An effect on UGE superior to that of selective SGLT2 inhibition in preclinical studies was observed (unpublished results); however, this has not been tested in the clinical setting. 32 A recent study showed that glucagon increases energy expenditure and decreases adipose tissue expansion in humans. value of up to 70% inhibition of renal glucose reabsorption, which is higher than that previously reported with SGLT2 inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…An effect on UGE superior to that of selective SGLT2 inhibition in preclinical studies was observed (unpublished results); however, this has not been tested in the clinical setting. 32 A recent study showed that glucagon increases energy expenditure and decreases adipose tissue expansion in humans. value of up to 70% inhibition of renal glucose reabsorption, which is higher than that previously reported with SGLT2 inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, high leptin and low ghrelin suppress the appetite, while low GLP-1 and glucagon contribute to appetite stimulation. The final effect on a child will also depend on meal content, the amount of high-fat and sugar, including fructose, the amount and distribution of body and liver fat content, the effects on insulin sensitivity and glucose metabolism, the basal nutritional status, gonadal status, exercise level, the integrity of the brain-gut axis, and their genetic susceptibility for diabetes mellitus (Bouret, 2013;Pettus et al, 2013;Korek et al, 2013;Shah and Vella, 2014;Liu et al, 2014aLiu et al, , 2014bLiu et al, , 2014cLaughlin,2014). Low levels of ghrelin are of concern in children given its involvement in the regulation of growth hormone, memory and learning, food addiction and neuroprotection (Albarran-Zeckler et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In mice, GLP-1 excretion is circadian, with larger amounts being released in the evening, and is highly entrained by feeding behavior [82]. GLP-1 affects satiety in the central nervous system [83] and can influence metabolic homeostasis by affecting hepatic gene expression. GLP-1 receptor activation in hepatocytes increases cAMP production as well as peroxisome proliferator-activated receptor α (PPARα) and acetyl-CoA oxidase expression, both of which are involved in fatty acid oxidation.…”
Section: Gut Signaling and Feeding Entrainmentmentioning
confidence: 99%